Character Education of Tolerance and Love for the Homeland in the Independent Study Curriculum in Junior High Schools - Nasution, Marwah; Safitri, Islamiani; Harahap, Risma Delima (Jurnal Pedagogi dan Pembelajaran, 2023)
The low values ​​of the character of tolerance and love for the homeland in students today are due to the lack of application and instilling the character values ​​of tolerance and love for the homeland in everyday life and the school environment. This study aims to assess and measure the character of tolerance and love for the motherland in supporting the independent learning curriculum. This research belongs to the type of quantitative research with a descriptive approach. The population in this study was 183 junior high school students, with a sample of 165 students who filled out the questionnaire. Data collection in the study was carried out using the questionnaire method, with the research instrument in the form of a closed questionnaire presented in the form of questions. The data obtained in the study were then analyzed using descriptive statistical data analysis techniques. The results of the data analysis show that the characters of tolerance and love for the homeland of class VII1, VII-5, VIII-2, VIII-4, IX-1, and IX-4 are students of class VII-1, as much as 97.93% and the percentage for The character of love for the country is 94.82%, the character for tolerance for class VII-5 has a percentage of 90.31%, the character for love for the country for class VII-5 has a percentage of 89.68%, for class VIII-2 the percentage of character values ​​for tolerance is 93.33 %, for class VIII-2 the percentage of love for the motherland is 83.8%, for class VIII-4 the character for tolerance is 85.66%, for class VIII-4 the character for love for the country is 81.66%, for class IX-1 character tolerance as much as 93.07%, class IX-1 the character of love for the country as much as 94.23%. The results of the percentage of class IX-4 on the character of tolerance have a percentage of 97.66%. Based on the results of this analysis, it can be concluded that the characteristics of Tolerance and Love for the Motherland in Supporting the Free Learning Curriculum are very good.